2011
DOI: 10.1080/17470218.2011.603427
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Coordination between Performing Musicians

Abstract: Many common behaviours require people to coordinate the timing of their actions with the timing of others' actions. We examined whether representations of musicians' actions are activated in coperformers with whom they must coordinate their actions in time and whether coperformers simulate each other's actions using their own motor systems during temporal coordination. Pianists performed right-hand melodies along with simple or complex left-hand accompaniments produced by themselves or by another pianist. Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
92
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 46 publications
13
92
1
2
Order By: Relevance
“…Producing and learning music likely involves even greater EF demands. For example, music is most often played in coordination with others (Palmer, 2013), which requires switching between multiple auditory streams (Loehr, Kourtis, Vesper, Sebanz, & Knoblich, 2013) and adjusting to other performers (e.g., Loehr & Palmer, 2011;Moore & Chen, 2010). Thus music performance may be associated with relatively general switching advantages, and musicians have indeed been found to outperform non-musicians on switching tasks (Hanna-Pladdy & MacKay, 2011;Moradzadeh, Blumenthal, & Wiseheart, 2014; see also Bugos, Perlstein, McCrae, Brophy, & Bedenbaugh, 2007;Zuk, Benjamin, Kenyon, & Gaab, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Producing and learning music likely involves even greater EF demands. For example, music is most often played in coordination with others (Palmer, 2013), which requires switching between multiple auditory streams (Loehr, Kourtis, Vesper, Sebanz, & Knoblich, 2013) and adjusting to other performers (e.g., Loehr & Palmer, 2011;Moore & Chen, 2010). Thus music performance may be associated with relatively general switching advantages, and musicians have indeed been found to outperform non-musicians on switching tasks (Hanna-Pladdy & MacKay, 2011;Moradzadeh, Blumenthal, & Wiseheart, 2014; see also Bugos, Perlstein, McCrae, Brophy, & Bedenbaugh, 2007;Zuk, Benjamin, Kenyon, & Gaab, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on music and coordination have focused primarily on note-to-note temporal synchrony (23), including how it is modulated by the partner (24)(25)(26)(27)(28)(29) and the role of perceptual information (30)(31)(32)(33). A few studies have attempted to describe temporal synchronization among musicians using mathematical models (34)(35)(36).…”
Section: Significancementioning
confidence: 99%
“…On this account, internal models in the cerebellum [49] commune with cortical areas, including those subserving motor simulation [100,101]. It is owing to this recruitment of the observer's motor system that internal models are calibrated to the observer's own action style [28,42,54].…”
Section: (B) Neural Bases Of Real-time Coordination Skillsmentioning
confidence: 99%
“…In musical contexts, mutual temporal adaptation may, additionally, contribute to ensemble cohesion by enhancing the similarity of co-performers' playing styles. Research with experimental tasks requiring piano duet performance [17,28] and dyadic finger tapping [29,30] has demonstrated that compensatory adjustments associated with error correction lead to co-dependencies, whereby successive time intervals produced by two interacting individuals tend to be similar in duration. Furthermore, a recent study employing an experimental task in which paired musicians tapped in alternation with an isochronous auditory pacing signal (analogous to two jazz soloists coordinating complementary parts with a rhythm section) found similarities between successive asynchronies produced by alternating individuals' taps relative to the pacing tones [31].…”
Section: (I) Mutual Temporal Adaptationmentioning
confidence: 99%
See 1 more Smart Citation